ANALISIS PENGARUH SEKTOR PERIKANAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN MIMIKA - Fitriyani Gaurahman; I Nyoman Putu Arka (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
This study aims to determine the potential of the fishery sector to be abase or non-base sector in the economy of Mimika regency and to find out the influence of the fishery sector on the economic growth of mimika regency. The research method used is associative and descriptive. Data collection techniques used were interviews and documentation. Data analysis tecniques used are DLQ analysis and simple regression analysis. The results showed that: (a) the average value of DLQ the fishery sector is a base sector in Mimika regency; and (b) the fishery sector has a significant effect on economic growth in Mimika regency